The death of Caligula : Josephus Ant. Jud. xix 1-273 - Josephus, Flavius (Liverpool University Press, 2013)
Emperor Gaius 'Caligula' was assassinated in January AD 41. It seemed that the dynasty of the Caesars was over, and republican rule restored; but a military coup by the Praetorian Guard set up Gaius' uncle Claudius as emperor. A detailed contemporary account of the plot and its aftermath was incorporated by the historian Josephus into his Antiquities of the Jews, as an example of the providence of God. This is a translation of that unjustly neglected narrative, one of the most important texts in Roman imperial history, with an introduction and historical commentary to bring out its full significance